PHYSICAL THERAPY OF MILITARY SERVICEMEN AFTER AMPUTATIONS (Physical Culture and Sport: Scientific Perspective, 2023)
Rehabilitation of military personnel as a result of military conflicts or traumatic events is an urgent and important task of the health care industry. Unfortunately, as a result of active hostilities, a similar situation is currently taking place in Ukraine, and the number of wounded military personnel and civilians who need proper assistance from various specialists of the multidisciplinary team is increasing every day. The purpose of the study: to theoretically substantiate the peculiarities of physical therapy of military personnel after amputations. Research methods. The work used the methods of the theoretical level of research: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature. Results. The general scientific approach to the physical rehabilitation of soldiers with amputations is based on the implementation of innovative methods, the involvement of multidisciplinary teams of specialists and the constant monitoring of results for the constant improvement of rehabilitation programs. Preparation of the patient for prosthetics begins only after the removal of the sutures, with special attention to the formation of the stump. The stump should have the correct shape, be painless, provide stable support and be strong enough to withstand the load. Initially, mobility is restored in the preserved joints of the amputated limb. When reducing pain and increasing mobility in these joints, exercises for the muscles of the stump are included in the therapy. Conclusions. Physical therapy of military amputees is a complex and multifaceted process aimed at restoring physical functionality, psychological comfort, and social integration of combatants who have become victims of limb loss. This process is based on the principles of individualization, complexity and phasing. Timely application of physical therapy can significantly speed up the process of returning servicemen to a full-fledged life.
Keywords: injuries; amputation; functional state; working capacity; military personnel